2014
DOI: 10.1111/bjd.13513
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of delphinidin reduces psoriasiform lesions in the flaky skin mouse model by inducing epidermal differentiation and inhibiting inflammation

Abstract: Summary Background Psoriasis is a chronic inflammatory skin disease characterized by hyperproliferation and aberrant keratinocyte differentiation. We have shown that treatment of reconstituted human skin with delphinidin, an anthocyanidin, present in pigmented fruits and vegetables, increased the expression and processing of caspase-14, which is involved in cornification. Delphinidin also increases the expression of epidermal differentiation marker proteins. Objectives To determine whether topical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 75 publications
(184 reference statements)
0
26
0
Order By: Relevance
“…NF-κB can regulate expression of many cellular factors and regulate inflammatory reactions. Abnormally activated NF-κB may launch the apoptosis of neurons in trauma of central nervous system, excitotoxic injury, ischemic damage and neurodegenerative disease (12). NF-κB is abnormally activated following SCI, activating inducible nitric oxide synthase in neurons (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NF-κB can regulate expression of many cellular factors and regulate inflammatory reactions. Abnormally activated NF-κB may launch the apoptosis of neurons in trauma of central nervous system, excitotoxic injury, ischemic damage and neurodegenerative disease (12). NF-κB is abnormally activated following SCI, activating inducible nitric oxide synthase in neurons (7).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of various genes in SCI is regulated by NF-κB, including the expression of pro-inflammatory cell factors, such as TNF-α, IL-1β and IL-6, as well as proteases, such as matrix metalloproteinase (7). Pal et al (12) reported that delphinidin reduces psoriasiform lesions by inducing epidermal differentiation and inhibiting inflammation in flaky skin mice. Cho et al (9) suggested that delphinidin inhibited extracellular matrix production in nasal polyp-derived fibroblasts through the MAPK/NF-κB signaling pathway induced by TGF-β1 stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sos1, as a binding protein of Ras, participates in the promotion of epithelial cell growth via regulating epithelial growth factor receptor signal 41 . Krt10 and Krt76, had been shown to regulate epithelial cell differentiation and proliferation 42 . Ribosome production factor 2 homolog (Rpf2) is a mutual‐action relevant protein of Ki‐67 that is a marker of cell proliferation 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In psoriatic skin, lymphocytes may alter the epidermal growth resulting in keratinocyte hyperproliferation and abnormal differentiation of apoptotic cells. 104 Various experimental animal models have been developed for psoriasis, namely, asebia mouse, 105 flaky skin mouse, 106 ultraviolet ray-B induced photodermatitis model, 107 genetically modified models of psoriasiform skin diseases, 108 and mouse tail model. [56][57][58][59][60] In this study, mouse tail model was selected to to avoidance of direct contact of its acidic functional group (−COOH), the trigger factor for irritation episodes, with the SC of the skin.…”
Section: Histopathologic Examinationmentioning
confidence: 99%